Pattern recognition : 39th German Conference, GCPR 2017, Basel, Switzerland, September 12-15, 2017, Proceedings /: 39th German Conference, GCPR 2017, Basel, Switzerland, September 12-15, 2017, Proceedings. (2017) - Unknown
No abstract available